2017
DOI: 10.1038/ni.3713
|View full text |Cite|
|
Sign up to set email alerts
|

Gut microbial metabolites limit the frequency of autoimmune T cells and protect against type 1 diabetes

Abstract: Gut dysbiosis might underlie the pathogenesis of type 1 diabetes. In mice of the non-obese diabetic (NOD) strain, we found that key features of disease correlated inversely with blood and fecal concentrations of the microbial metabolites acetate and butyrate. We therefore fed NOD mice specialized diets designed to release large amounts of acetate or butyrate after bacterial fermentation in the colon. Each diet provided a high degree of protection from diabetes, even when administered after breakdown of immunot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
504
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 569 publications
(561 citation statements)
references
References 57 publications
26
504
1
6
Order By: Relevance
“…Recently, in the non-obese diabetic (NOD) mouse model, T1D severity was shown to be inversely correlated with levels of acetate and butyrate, microbial metabolites. When these metabolites were replaced in the diet, NOD mice were protected from the development of T1D [202]. Furthermore, the authors found that acetate supplementation decreased the activation of autoreactive T cells while butyrate supplementation increased the number and function of regulatory T cells, thereby preventing autoimmune development of T1D [202].…”
Section: Barrier Pathophysiology In Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in the non-obese diabetic (NOD) mouse model, T1D severity was shown to be inversely correlated with levels of acetate and butyrate, microbial metabolites. When these metabolites were replaced in the diet, NOD mice were protected from the development of T1D [202]. Furthermore, the authors found that acetate supplementation decreased the activation of autoreactive T cells while butyrate supplementation increased the number and function of regulatory T cells, thereby preventing autoimmune development of T1D [202].…”
Section: Barrier Pathophysiology In Diseasementioning
confidence: 99%
“…When these metabolites were replaced in the diet, NOD mice were protected from the development of T1D [202]. Furthermore, the authors found that acetate supplementation decreased the activation of autoreactive T cells while butyrate supplementation increased the number and function of regulatory T cells, thereby preventing autoimmune development of T1D [202]. Several studies examining different probiotics have shown that altering the microbiome can influence both the inflammatory state of the intestine as well as prevent the progression of T1D [203].…”
Section: Barrier Pathophysiology In Diseasementioning
confidence: 99%
“…SCFAs exert their effects not only in the gut but also in distant organs by dampening immune responses that are uncontrolled in patients on a low-fiber Western diet (Thorburn et al, 2014). High-fiber diets have been shown to ameliorate metabolic and allergic diseases mainly through their microbiota-dependent fermentation to SCFAs that promote tissue barrier integrity, mucus production, IgA secretion, and regulatory T cell (Treg) differentiation, thereby supporting an anti-inflammatory environment (Mariño et al, 2017; Thorburn et al, 2014). However, little is known about the beneficial effects of a high-fiber diet in autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids can be classified into short‐ (SCFA, <10 carbon atoms), medium‐ (MCFA, 10–14 carbon atoms), long‐ (LCFA, 16–20 carbon atoms), and very‐long‐chain fatty acids (VLCFA, >20 carbon atoms). SCFAs were recently found to ameliorate EAE, as well as other autoimmune diseases, such as type 1 diabetes, by expanding lamina propria–derived T reg cells through suppression of the JNK1 and p38 pathway 98, 125. In line with these studies, SFCAs also increase the number of colonic T reg cells in an experimental model of inflammatory bowel disease 126, 127.…”
Section: Long‐ Versus Short‐chain (Saturated) Fatty Acidsmentioning
confidence: 71%